2021
DOI: 10.1186/s13104-021-05496-w
|View full text |Cite
|
Sign up to set email alerts
|

Lack of detection of the Middle East respiratory syndrome coronavirus (MERS-CoV) nucleic acids in some Hyalomma dromedarii infesting some Camelus dromedary naturally infected with MERS-CoV

Abstract: Objective The Middle East respiratory syndrome coronavirus (MERS-CoV) is one of the zoonotic coronaviruses [Hemida Peer J 7:e7556, 2019; Hemida et al. One Health 8:100102, 2019]. The dromedary camels remained the only known animal reservoir for this virus. Several aspects of the transmission cycle of the virus between animals, including arthropod-borne infection, is still largely unknown. The main objective of the current work was to study the possibility of MERS-CoV transmission through some a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…For instance, they have been involved in the evolution of several human coronaviruses, but their exact role in the transmission of MERS-CoV remains unclear [ 53 ]. Hence, we screened our samples for this virus as well, including the collected ticks, although MERS-CoV infection does not involve a significant viremic period, and it has recently been shown that apparently neither ticks nor rodents play a role in the transmission cycle [ 53 , 54 ]. Concordant with the findings of Hemida et al, but in contrast to our findings with CCHFV [ 7 , 9 ], in this cohort we could not find any indications for the involvement of rodents or rodent-associated ticks in the transmission of CCHFV or MERS-CoV.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, they have been involved in the evolution of several human coronaviruses, but their exact role in the transmission of MERS-CoV remains unclear [ 53 ]. Hence, we screened our samples for this virus as well, including the collected ticks, although MERS-CoV infection does not involve a significant viremic period, and it has recently been shown that apparently neither ticks nor rodents play a role in the transmission cycle [ 53 , 54 ]. Concordant with the findings of Hemida et al, but in contrast to our findings with CCHFV [ 7 , 9 ], in this cohort we could not find any indications for the involvement of rodents or rodent-associated ticks in the transmission of CCHFV or MERS-CoV.…”
Section: Discussionmentioning
confidence: 99%
“…Searching for some new unknown reservoir/s that may contribute to the sustainability and enhance the continuous transmission of the virus among dromedary camels is still one of the main research priorities in the epidemiology of MERS-CoV. Some recent studies showed the lack of detection of MERS-CoV-RNAs in some species of ticks infesting some MERS-CoV naturally infected camels (Hemida et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Searching for some new unknown reservoir/s that may contribute to the sustainability and enhance the continuous transmission of the virus among dromedary camels is still one of the main research priorities in the epidemiology of MERS‐CoV. Some recent studies showed the lack of detection of MERS‐CoV‐RNAs in some species of ticks infesting some MERS‐CoV naturally infected camels (Hemida et al., 2021b). Another recent study reported the lack of detection of MERS‐CoV‐RNAs in samples from some species of rodents that shared their habitat with some index positive camel population (Hemida et al., 2021a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How I. scapularis ticks might become infected with SARS-CoV-2 is unclear. Based on a study of camels infected with Middle East Respiratory Syndrome coronavirus (MERS-CoV), the Hyalomma dromedarii ticks present on these animals did not demonstrate the presence of MERS-CoV [8]. Although multiple other viruses have been found in or on I. scapularis ticks collected before COVID-19 first appeared in the USA, none was a coronavirus [9].…”
mentioning
confidence: 99%